2015
DOI: 10.1002/jsfa.7188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synthetic and natural water‐absorbing soil amendments on photosynthesis characteristics and tuber nutritional quality of potato in a semi‐arid region

Abstract: Amendment treatment with PAM + HA always had the greatest effect on photosynthesis characteristics and tuber nutritional quality among all amendment treatments and thus merits further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(78 reference statements)
1
2
0
Order By: Relevance
“…Lentz ( 2015 ) observed that applying PAM to the soil increased the formation of soil water-stable aggregates, improved soil water conductivity, inhibited soil water evaporation, increased soil water retention, and thus improved the crop growth environment. Xu et al ( 2016 ) found that soil amendment with PAM improved the leaf net photosynthetic rate, stomatal conductance, and transpiration rate of potato compared with the control, and similar results were observed in our experiment. Wei et al ( 2011 ) found that different PAM treatments had no significant effect on the photosynthetic rate of maize, whereas the application of PAM decreased the transpiration rate compared with the control.…”
Section: Discussionsupporting
confidence: 90%
“…Lentz ( 2015 ) observed that applying PAM to the soil increased the formation of soil water-stable aggregates, improved soil water conductivity, inhibited soil water evaporation, increased soil water retention, and thus improved the crop growth environment. Xu et al ( 2016 ) found that soil amendment with PAM improved the leaf net photosynthetic rate, stomatal conductance, and transpiration rate of potato compared with the control, and similar results were observed in our experiment. Wei et al ( 2011 ) found that different PAM treatments had no significant effect on the photosynthetic rate of maize, whereas the application of PAM decreased the transpiration rate compared with the control.…”
Section: Discussionsupporting
confidence: 90%
“…As a result of this, germination potential has some influence. While adding no-treatment SAPs, because the moisture is not absorbed by SAPs the water can be directly used by the seed and SAPs can reserve more water for plant germination by absorbing excess moisture and reducing the amount of direct evaporation [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is evident from the literature that the performance of SAP-Hs depends on many variables, such as the quality of irrigating water, environmental conditions, type and chemical composition of soil, and types of plants (Levy & Warrington, 2015). The application of inappropriate types or incorrect amounts of SAP-Hs can reduce soil ventilation, expose plants to diseases, or lead to nutrient deficiencies in crops (Xu et al, 2016a).…”
Section: Superabsorbent Hydrogels For Soil Conditioning and Water Manmentioning
confidence: 99%